Persepsi Sivitas Akademika Universitas Andalas Terhadap Mahasiswi Bercadar - Athiyah Kurnia Sari; Alfan Miko; Indraddin Indraddin (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
This research is motivated by the perception of Andalas University academics towards veiled female students who disagree with the use of the veil. This study aims to determine the perception of the academics of Andalas University towards veiled female students from the aspects of knowledge, attitudes and actions. The study was conducted using a quantitative approach with descriptive analysis design. The population in the study were students and lecturers at Andalas University from five faculties. The sample taken amounted to 380 people consisting of lecturers and students, using the proportionate random sampling technique and in collecting data using a questionnaire. The theory used is Functional Structure pioneered by Emile Durkheim, which is classified as a social fact. In analyzing this functionalist theory, society is a system consisting of interconnected, related and balanced parts, then all social structures are integrated into a unity and have a function that different but still creates order and the whole elements will adapt to each other's changes in society both internal and external. This social fact is a way of thinking, a way of feeling, a way of acting, a way of being that is outside the individual (external), general, and coercive that can explain the perception of the academics of Andalas University towards veiled female students who are social facts. The average score (mean) is 3.72 where this score shows the perception of Andalas University academic community towards veiled students on a positive or good interval scale, which is seen from the level of knowledge, attitudes and actions.